Dr. ENHANCING WEED CONTROL EFFICACY OF TWO PREEMERGENCE HERBICIDES IN MAIZE/ JACKBEANS AND MAIZE/GROUNDNUT INTERCROP IN DERIVED SAVANNA AGRO-ECOLOGY: WEED CONTROL EFFICACY OF TWO PREEMERGENCE HERBICIDES IN MAIZE/ JACKBEANS AND MAIZE/GROUNDNUT INTERCROP IN DERIVED SAVANNA AGRO-ECOLOGY - Adeyemi, Olusegun Raphael; Eni, Enor; Lagoke, Toyosi Olayiwola; Ebenezer, Osebekwin (Journal of Agricultural Sciences (Belgrade), 2021)
The inability of pre-emergence herbicides alone to give season-long weed control in maize production justifies the need for supplementary weed control. Field trials were conducted to evaluate intercropped groundnut and jackbean for enhanced weed control efficacy of two pre-emergence herbicides in maize production, in 2013/2014 and 2015 cropping seasons at Federal University of Agriculture, Abeokuta, Nigeria. The experiment was arranged in split-plot fitted in a Randomized Complete Block Design with three replications. Main plots consisted of eight weed control treatments of commercially formulated mixture of Prometryne (20%) + Metolachlor (20%); Prometryne (13%) + Acetochlor (38%) each at 2.4 kg a.i/ha, 1.6 kg a.i/ha with and without supplementary hoe-weeding, two hoe-weedings and weedy check. Sub-plot treatments consisted of eight cropping patterns [sole maize, maize-jackbean and maize-groundnut intercrops, each at two spacings (100 x 37.5 cm2 and 75 x 50 cm2) and sole crops of jackbean and groundnut]. All the weed control methods significantly reduced (p<0.05) weed dry matter compared to weedy check by 10-81%. Maize grain yields (1.4 - 5.2 tha-1) were similar for all plots with the weed control methods, except in 2015 late season but significantly depressed (21–48%) on those weed-infested throughout. Intercropped jackbean and groundnut with maize significantly suppressed weed growth relative to sole crops of maize, jackbean or groundnut by 20-67%. Efficacy of pre-emergence herbicides in this study was therefore enhanced by intercropping of maize with jackbean and groundnut at 75 x 50 cm2 and 100 x 37.5 cm2 spacing in the early seasons.